ESRA19-0105 Comparison of ultrasound guided continuous transmuscular quadratus lumborum block with ultrasound guided continuous psoas compartment block for total hip arthroplasty – a randomised controlled trial. (30th August 2019) - Chhabra, A; Balakrishnan, A; Kumar, A; Talawar, P; Subramaniam, R; Trikha, A; Dehran, M; Malhotra, R
Abstract : Background and aims: The transmuscular quadratus lumborum block (QLB) is thought to result in spread of local anaesthetic to thoraco-lumbar paravertebral space. the primary objective was to compare VAS at 6 hours with continuous QLB and continuous psoas compartment block (PCB) for unilateral THA under general anaesthesia (GA). Secondary objectives: dermatomes blocked, 0–24hr VAS and fentanyl consumption, quality of recovery. Methods: After ethics committee approval 63 consenting ASA I-III patients, 18–70 years were randomized to PCB or QLB group. All blocks were performed in lateral position, needle tip directed between QL and psoas major (QLB group) or lumbar plexus confirmed by quadriceps twitch (PCB group). Bolus 0.4 ml/kg 0.25% ropivacaine, catheter inserted. Dermatomes assessed at 30 min, followed by standard anaesthesia (blinded anaesthesiologist) and infusion of 0.1 ml/kg/hr ropivacaine for 24hr. Fentanyl (0.5 mcg/kg) administered for increase in heart rate or MAP 20% above baseline. Postoperatively, all received PCA fentanyl, rescue morphine. Results: The 6 hour VAS at rest and movement was comparable between groups [rest: 25.34±14.25 (PCB); 27.3±9.6 (QLB), p=0.53], [movement: 35.1±23 PCB;, 38.6± 17 QLB (p=0.53)], but the upper limit of mean difference of VAS (7.1 on rest, 12.2 on movement, 90% CI) between groups was not acceptable. Total 24hr fentanyl requirement was significantly more in the QLB [1212.5 mcg (300–2345) vs PCB group [635 mcg (100–1645), median (range)], (p=0.0004). L1-3 dermatomes were blocked in PCB vs T11-12 in QLB group, 11 PCB patients had motor weakness 30 minutes post block. Conclusions: Continuous USG QLB cannot replace PCB for analgesia in patients undergoing unilateral THA under GA.